2019
DOI: 10.7150/thno.31144
|View full text |Cite
|
Sign up to set email alerts
|

In-depth serum proteomics reveals biomarkers of psoriasis severity and response to traditional Chinese medicine

Abstract: Serum and plasma contain abundant biological information that reflect the body's physiological and pathological conditions and are therefore a valuable sample type for disease biomarkers. However, comprehensive profiling of the serological proteome is challenging due to the wide range of protein concentrations in serum. Methods : To address this challenge, we developed a novel in-depth serum proteomics platform capable of analyzing the serum proteome across ~10 orders or magnitude by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 76 publications
4
87
0
Order By: Relevance
“…Using these reference sequences, we prepared a peptide library containing 966 peptides representing SARS-CoV-2 proteins, in which each peptide was 15 amino acids long with a 5 amino acid overlap. All peptides were labeled with a C-terminal biotin group and printed onto a three-dimensional (3D) modified microscope slide using biotin–streptavidin chemistry, 21 such that the peptides were immobilized on the slide via their C-terminus. Full-length SARS-CoV-2 N protein, full-length E, and five S truncated proteins were also printed ( Supporting Information Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using these reference sequences, we prepared a peptide library containing 966 peptides representing SARS-CoV-2 proteins, in which each peptide was 15 amino acids long with a 5 amino acid overlap. All peptides were labeled with a C-terminal biotin group and printed onto a three-dimensional (3D) modified microscope slide using biotin–streptavidin chemistry, 21 such that the peptides were immobilized on the slide via their C-terminus. Full-length SARS-CoV-2 N protein, full-length E, and five S truncated proteins were also printed ( Supporting Information Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The antibody microarrays and sera screening were processed as previously described (10). Briefly, 10 μL of serum were diluted with 90 μL phosphate buffered saline (PBS; pH 7.4) and labeled with 1 μL of NHS-PEG4-Biotin (20 After removing the excess biotin molecules, the biotinylated proteins were dissolved in 400 μL of PBS containing 5% milk (w/v).…”
Section: Screening Of Covid-19 Serum Proteome Using Antibody Microarraysmentioning
confidence: 99%
“…As of May 04, 2020, 3 (8,9). However, to date, there is neither a vaccine to prevent COVID-19 nor an effective medicine to treat In this study, a comprehensive analysis of serological proteins from patients in the early stages of COVID-19 or influenza was performed using an antibody microarray developed in our laboratory (10). A large number of differentiallyexpressed proteins were identified that mediates diverse immune signaling by guest on November 3, 2020 pathways related to viral infection, the inflammatory response, and immune cell activation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…e unknown pathogenesis has brought difficulties to the treatment, without curative approaches against psoriasis at present. Traditional Chinese medicine (TCM) has unique advantages in treating psoriasis, which can play therapeutic roles through multiple targets and multiple pathways, corresponding to the dysfunction of various pathways underlying the pathogenesis of psoriasis [10][11][12][13]. However, TCM also has defects.…”
Section: Introductionmentioning
confidence: 99%